Alternate Paths to Excellence - Cross, K. Patricia; California Univ., Berkeley. Inst. of Governmental Studies ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
In the history of this country there have been 3 major philosophies about who should go to college: (1) the aristocratic philosophy, (2) the meritocratic philosophy, and (3) the philosophy of egalitarianism, which came into vogue in the 60's. This has meant that the greatest rate of increase in college attendance during the last 10 years has been by members of the lower socioeconomic groups and those with lower academic standing. The 60's emphasized gaining access to higher education for these students; the 1970's must concentrate on accommodation, i.e., changing the system to fit the student. The access system, which is a unidimensional model, attempts to move the marginal student closer to the core through remediation of academic or motivational deficiencies; the system is designed for orderly progression through a funnel or sorting system, effectively eliminating those who don't fit the system. Though systematic educational activities are now going on outside the regular system, i.e., on the educational periphery, equality of educational opportunity would be enhanced by the creation of new educational models that will permit easy movement between the core and periphery. This paper discusses new models for education: developing new cores of excellence, and developing lifelong learning models. It also makes recommendations for policies and programs to institute new educational models. (AF)
ERIC Note: Paper prepared for the Education Task Force of the White House Conference on Youth.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Disadvantaged Youth; Educational Change; Educationally Disadvantaged; Equal Education; Higher Education